PENGEMBANGAN MODEL SERVICE QUALITY PADA INDUSTRI JASA OTOMOTIF DI ”EIFISIENSI TOUR AND TRAVEL” TULUNGAGUNG - Tali Roso Susilo; Sri Rahayuningsih; Heribertus Budi Santoso (Universitas Kadiri, 2019)
In this study, an analysis of the development of a quality service model for land transportation service providers, namely Eiffficiency Tour and Travel, is located in Wajak Kidul, Boyolangu District, Tulungagung Regency. In reality, there are still many matters related to service quality ignored by Tour and Travel Efficiency in the field. This is evidenced by the events that occur in the reasonably extensive list of customer complaints. This study refers to the survey method carried out by collecting information from samples obtained from a place to generalize the extent to which the population from which the sample was taken. In this final project research, the authors researched transportation service providers.